Found in transition eaudiobook A mother's evolution during her child's gender change. - Hassouri, MD, Paria (Tantor Media, 2020)
What do you do when, just before Thanksgiving at your mother's, your fourteen-year-old son asks you to iron the dress he recently purchased and plans to wear? Listeners learn the answer and much more in this wonderfully frank, loving, and practical account of parenting a transgender teen. Paria Hassouri chronicles what amounts to a dual transition: as her child transitions from male to female, she navigates through anger, denial, and grief to eventually arrive at acceptance. Despite her experience advising other parents in her work as a pediatrician, she was blindsided by her child's gender identity. Her journey forces her to reckon with how her own childhood as a brown kid in a white world led her to sometimes parent with fear rather than love. Hassouri discovers her capacity to evolve, as well as what it really means to parent and the deepest nature of unconditional love. At its heart, Found in Transition is a universally inspiring portrait of what it means to be a family.